About the methodology of system synthesis of decision-makings and its procedures automation - D. P. Oleynikov; L. N. Butenko (Открытое образование (Москва), 2016)
Purpose. The problem qualitative assessment of technologies and innovations, which cannot be solved without modern methods and decision support systems, is currently particularly relevant. The reason for this is the increasingly increasing amount of heterogeneous information, which should take into account the decision maker. Reduction of the allowable period of decision-making also has a signifi cant impact on this process. These reasons are refl ected in the problems of network-centric warfare, nuclear management, forecasting, and conceptual design. It actualizes the problem of the synthesis of new methods of decision-making that will effectively solve the problem of choice of alternatives in those problem areas where the application of existing methods of decision-making is unfounded or inadmissible. The complexity of the process of creation of new decision-making methods caused by the high degree of utilization of cognitive processes. In accordance with the system-wide development trends the designer in the process of synthesis of the decision-makings should take a system (or group of systems) which implements certain cognitive operations. The first step towards the creation of such a group of systems is the development of methodology of the system synthesis of decision-makings.Materials and methods. The scope of research are approaches to the synthesis of systems, and in particular – the synthesis of decision-makings. On the basis of multidimensional analysis and generalization of approach the methodology was developed, which consists of the main stages - goal setting, goal achievement and variations of the target system. Within each of the stages a wide variation of operations is possible to be used, which applied depending on the available data, obtained from the analysis of the subject area. With the use of the methodology obtained a number ofdecision-making methods, and their creation was carried out without the use of computer equipment, which require signifi cant time expenses on the development of appropriate solutions. Therefore, it was decided to develop an automated system to improve the effectiveness of the implementation of a number of methodology procedures.Results.During the study were identifi ed use cases of the system, in accordance with which were formed the conceptual and technical architecture of the system, highlights the key subsystems of the reference data, knowledge about the methods of decision-making and synthesis strategies, and identifi es their development tools. As the database used by the DBMS MS SQL Server, as the client side – Borland Delphi.Conclusion. Due to the high complexity of formalization of intellectual, creative, methodologies operations, the focus of automation is the support of conceptual analysis of the decisionmakings subject area and formation on its basis the knowledge base of intellectual operations together with their characteristic features, aimed to combine operations that make up the group of methods of synthesis strategies decision-making and implementation of the search function on the basis of a intellectual operations knowledge base.